Alagille Syndrome: A Novel Mutation in JAG1 Gene - Rita Fischetto; Viviana V. Palmieri; Maria E. Tripaldi; Alberto Gaeta; Angela Michelucci; Maurizio Delvecchio; Ruggiero Francavilla; Paola Giordano (Frontiers Media S.A., 2019)
Alagille syndrome is an autosomal dominant multisystem disorder with variable phenotypic penetrance, caused by heterozygous mutations in JAG1 or NOTCH2, encoding for the components of the Notch signaling pathway. In this paper, we described a novel mutation not yet reported in literature. This 3-years old male child was referred to our Clinical Genetics Unit because of delayed psychomotor development, systolic murmur, dysmorphic facial features, and hypertransaminasemia. The novel JAG1 heterozygous c.2026delT variant in exon 16 was found. JAG1 mutations are classified as protein truncating and non-protein truncating, without any genotype-phenotype correlation. The detected mutation determines a stop codon (p.Cys676AlafsTer67) in the gene sequence, encoding a truncated protein. Our report broadens the spectrum of JAG1 gene mutations.